STUDI KASUS: TRANSMISSIBLE VENEREAL TUMOR (TVT) PADA ANJING GOLDEN RETRIEVER DI UPTD PUSKESWAN KOTA BUKITTINGGI - Lefiana, Delli (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2025)
Abstract Transmissible venereal tumor (TVT) is a tumor in dogs that originates from a somatic cell line that infects the male and female reproductive organs, caused by environmental factors, weather, temperature, and other factors. inside the animal's body. Clinical symptoms of TVT in dogs include decreased activity, bleeding from the foreskin, serous discharge, discharge, swelling in the penile region, and fleshy growth in the glans penis. The Golden Retriver arrived at UPTD Bukittinggi Puskeswan on March 7, 2022 with bloody urine, frequent stress and a temperature of up to 38.4ºC. In addition to the clinical symptoms, hematological tests, surgical resection of the tumor and histopathological examination of tumor cells were also performed. Histopathological examination results showed that the tumor cells were proliferative lymphocytes of uniform size, surrounded by stromal tissue, with macrophage cells, and lymphocytes with moderate mitotic index with the diagnosis of Tumor venereal transmission (TVT). The results of hematology examination showed that the dog had thrombocytopenia, increased lymphocytes and increased MCHC values.